(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In the article the theoretical approaches to the category «tourist clusters» were made, the synergetic and complementary effects from the existence of the tourist cluster in the region were clarified, examples of cluster formations in Ukraine are presented. The theoretical significance of regional tourist clusters is thoroughly investigated, advantages and disadvantages of their functioning are highlighted, constructive ways of solving are proposed, social and economic problems of the region through the spread of cluster groups.